(untitled) (Journal of Informatics Education and Research, 2025)
This study conducts a comprehensive bibliometric analysis of 1,520 articles indexed in Scopus from 2015 to 2024, examining the evolving research landscape on the relationship between the Circular Economy and consumer behaviour. The primary objective is to map the scientific network and contributions within this domain. The analysis highlights a significant increase in research interest, with 2022 and 2023 recording the highest publication output, amounting to 124 articles. Among the leading contributors, R. Mugge stands out for making substantial scholarly contributions, while Delft University of Technology emerges as the most affiliated institution in this field.